Strategi Pemasaran Keripik Singkong Di Desa Tanjung Jaya Kabupaten Garut (Kajian Hukum Ekonomi Syariah) - Wati, Ai; Ajwasyifa, Diani (STAI Al Musaddadiyah Garut, 2023)
Cassava Chips Entrepreneur is a cassava chip manufacturing business located in a residential area of RW 03, Tanjung Jaya Village, Banjarwangi District, Garut Regency. This entrepreneur in carrying out his business activities has implemented various marketing strategies which include product strategies, pricing strategies, distribution strategies, and promotional strategies. The formulation of the problem in this study is: 1. How is the Marketing Strategy for Buying and Selling Cassava Chips in Tanjung Jaya Village, Garut Regency Viewed from the Perspective of Sharia Economic Law? 2. What factors affect the marketing strategy of buying and selling cassava chips in Tanjung Jaya Village, Garut Regency? and the purpose of this study is to find out how the marketing strategy of buying and selling cassava chips in Tanjung Jaya Village, Garut Regency is viewed from the perspective of Sharia Economic Law and to find out what factors affect the marketing strategy of buying and selling cassava chips, Tanjung Jaya Village, Garut Regency. The research method used in this study is to use field research and qualitative approaches. The results of the study, that in practice it is in accordance with the principles of Sharia economic law, namely the fulfillment of the principle of Muawwanah, the principle of equity where property is not controlled by a group of people, the principle of adamul gharar, the principle of Al Bir At-Taqwa, except the principle of musharakah does not exist because the cassava chip company stands alone. Keywords: Marketing Strategy, Sharia Economic Law Study